Crustal structure of the Lazufre volcanic complex and the Southern Puna from 3-D inversion of magnetotelluric data: Implications for surface uplift and evidence for melt storage and hydrothermal fluids - Unsworth, Martyn (2023)
The Central Andes are unique in the global system of subduction zones in that a significant, high- altitude plateau has formed above a subduction zone. In this region, both subduction and the associated magmatism have been shown to vary in both space and time. Geophysical data have been invaluable in determining the subsurface structure of this region. Extensive seismic studies have determined the regional- scale distribution of partial melt in the crust and upper mantle. Magnetotelluric studies have been effective in providing independent constraints on the quantity and composition of partial melt in the crust and upper mantle. Geodetic studies have shown that a small number of volcanic centers exhibit persistent, long- term uplift that may indicate the formation of plutons or future eruptions. This paper describes a detailed study of the Southern Puna using magnetotelluric (MT) data. This region is located at the southern limit of the Central Andes in a region where a recent transition from flat- slab subduction to normal subduction has caused an increase in magmatism, in addition to hypothesized lithospheric delamination. It is also a region where an extensive zone adjacent to the volcanic arc is undergoing surface uplift, located near Volcán Lastarria and Cordon del Azufre (collectively called Lazufre). The main goals of the work are to define the crustal structure and to investigate processes that may cause surface uplift of relatively large regions not associated with active volcanism. As part of the PLUTONS project, MT data were collected on an east- west transect (approximately along 25°S) that extended across the Southern Puna, from Lazufre to north of Cerro Galan. The data were combined with previously collected MT data around Lazufre and inverted to give a 3-D resistivity model of the crust. The low resistivity of the crust resulted in limited sensitivity to mantle structure. A number of major crustal conductors were detected and included (1) a mid- crustal conductor extending eastward from the volcanic arc as far as the Salar de Antofalla; (2) an upper- to mid- crustal conductor located north of Cerro Galan; and (3) a conductor that rises westward from (1) and terminates directly beneath the region of surface uplift at Lazufre. These conductors are broadly coincident with the location of crustal low shear- wave anomalies. The conductive features were interpreted to be due to zones of partial melt stored in the crust, and petrological data were used to estimate melt fractions. Below Lazufre, it is likely that aqueous fluids contribute to the high conductivity, which is observed within the depth range of the inflation source, giving evidence that the surface uplift may be associated with both magmatic and hydrothermal processes.